Dynamic Changes in Lung Microbiota of Broilers in Response to Aging and Ammonia Stress - Chen, Jian; Jin, Ai; Huang, Lei; Zhao, Yan; Li, Yuwen; Zhang, Haotian; Yang, Xiaojun; Sun, Qingzhu (Frontiers in Microbiology, 2021)
Comprehensive microbial analysis has revealed that the lung harbors a complex variety of microbiota, and although the dynamic distribution of the lung microbiota in mice and laying hens of different ages is well established, this distribution has not been clarified in broilers of different ages. Here, we performed 16S rDNA gene sequencing of lung lavage fluid from broilers at 3 (3D), 7 (7D), 14 (14D), 21 (21D), and 35 (35D) days of age to evaluate changes in the composition of their lung microbiota. Upon examination of the composition and function of the broiler lung microbiota, we found that their maturation increased significantly with age. Specifically, the microbiota composition was similar between 7D and 14D and between 21D and 35D. The relative abundance of aerobic bacteria in the broiler lungs gradually increased as the broilers developed, whereas the relative abundance of potentially pathogenic bacteria reached its highest level at 3D. The relative abundance of predicted functions in microbiota was very similar among 3D, 7D, and 14D, whereas the Glycan Biosynthesis and Metabolism pathway in microbiota was enriched at 21D. These findings suggest that these metabolic pathways play critical roles in shaping broiler microbiota at these age stages. In addition, the short-term external ammonia stimulation significantly increased lung inflammation but did not significantly affect the lung microbiota. Taken together, these data reveal the dynamics of age-related changes in the microbiota of broiler lungs and the stability (the significant variation in the microbial composition) of these microbial communities in response to short-term ammonia stress. These findings provide new insights into the development of broiler lung microbiota and serve as a reference for subsequent studies to evaluate disease prevention in broilers subjected to of large-scale breeding.